ASSESSMENT OF MUSCLE FUNCTION LOSS USING THE CREATININE-CYSTATIN C RATIO AND BODY FAT IN TYPE 2 DIABETES MELLITUS (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to evaluate the ability of the creatinin/cystatin C ratio in combination with percent body fat and age factor in predicting the decline of muscle mass and function in patients with type 2 diabetes mellitus.Methods: A cross-sectional study of 93 patients with type 2 diabetes and 34 healthy controls recruited from the outpatient clinic of the University Medical Center Ho Chi Minh City - Campus 2. Appendicular skeletal muscle mass, appendicular skeletal muscle mass/body mass index, and percent body fat were measured using the InBody device. Muscle function was assessed using handgrip strength and walking time. Serum creatinine and cystatin C were used to calculate the creatinin/cystatin C ratio. Two predictive models were built: percent body fat + creatinin/cystatin C; and percent body fat + creatinin/cystatin C + age.Results: Higher creatinin/cystatin C values were associated with greater appendicular skeletal muscle mass/body mass index, stronger handgrip strength, and shorter walking time. For detecting low muscle mass, AUC increased from 0.8 to 0.82. For weak muscle strength, AUC improved from 0.65 to 0.75, and for prolonged walking time, from 0.67 to 0.70 after adding age. The full model for the highest discrimination capability.Conclusions: A combined model using creatinin/cystatin C and percent body fat provides strong predictive accuracy for identifying muscle impairment, and the addition of age further enhances performance
Keywords: Creatinine/cystatin C ratio, type 2 diabetes mellitus, sarcopenia, eGFR, BMI.